2021
DOI: 10.1007/s00198-021-05824-7
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral fractures are increased in rheumatoid arthritis despite recent therapeutic advances: a case-control study

Abstract: Prevalence and risk factors of vertebral fractures in postmenopausal RA women were assessed in 323 patients and compared with 660 age-matched women. Of patients, 24.15% had at least one vertebral fracture vs.16.06% of controls. Age, glucocorticoids and falls were the main fracture risks. Vertebral fractures were associated with disease severity. Introduction There is little quality data on the updated prevalence of fractures in rheumatoid arthritis (RA) that may have changed due to advances in the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
2
13
1
2
Order By: Relevance
“…The relation of disease activity to osteoporosis was investigated in a relatively high number of studies. Although neutral data were also published [ 46 ], the vast majority of reports found that in RA a higher disease activity is associated with bone loss and/or osteoporosis [ 47 , 48 , 49 , 50 ]. Indirectly, this association underlines the important role of the immunological disease process for systemic bone alterations in RA.…”
Section: Human Association Studiesmentioning
confidence: 99%
“…The relation of disease activity to osteoporosis was investigated in a relatively high number of studies. Although neutral data were also published [ 46 ], the vast majority of reports found that in RA a higher disease activity is associated with bone loss and/or osteoporosis [ 47 , 48 , 49 , 50 ]. Indirectly, this association underlines the important role of the immunological disease process for systemic bone alterations in RA.…”
Section: Human Association Studiesmentioning
confidence: 99%
“…[1][2][3][4][5] Patients with RA have approximately double the risk of osteoporosis 2,3 and two-to three-fold higher rates of fracture 1,4 compared with the general population; this increase in risk is most pronounced in patients with longer RA disease duration, chronically persistent inflammation, seropositive disease, use of corticosteroids, and low physical activity. 6,7 Other known risk factors for fracture include older age, smoking, lower body mass index (BMI), low bone mineral density (BMD), female sex, history of prior fracture, and the use of opioids, proton pump inhibitors, and antidepressants. 1,[8][9][10][11][12][13][14] Some studies in patients with RA have suggested that treatment with biologic disease-modifying antirheumatic drugs (DMARDs) and targeted synthetic DMARDs can reduce the loss of BMD and/or fracture risk, 10,15,16 potentially by controlling systemic inflammation and/or reducing use of glucocorticoid therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that patients with RA continue to have an elevated risk of fracture compared with the general population, despite recent improvements in the RA therapeutic landscape. 7,17 Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of RA. 18,19 Published preclinical data in animal models of RA suggest that tofacitinib may reduce osteoclastogenesis, stimulate osteoblast function and have a protective effect on BMD in the pro-inflammatory state of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fragility fractures in RA are not limited to the vertebral and proximal femur but can occur anywhere in the body, including the pelvis and metaphysis [ 9 ]. Some reports pointed out that incidence of vertebral fractures in RA patients was associated with high RA disease activity [ 10 , 11 ]. On the other hand, some studies have reported that the incidence of non-vertebral fractures in RA patients was high regardless of RA disease activity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%